Comparison between Audit Command Language and Interactive Data Analysis Software - Handoko, Bambang Leo; Angeline, Kitty; Petricia, Jessica; Hidayat, Maria Angelina (International Journal of Psychosocial Rehabilitation, 2020)
Computer Assisted Audit Tools and Techniques (CAATs) refer to the use of technology in assisting the implementation of audit procedures. Implementation of CAATs can add value to the audit process, because CAATs can be used to carry out functions or activities that are routine, so the audit process will focus more on data analysis and information reporting. One technique that can be used in implementing CAATs is Data Extraction and Analysis (DEA). In general, the implementation of the DEA technique involves the use of certain software specifically created for the implementation of the audit process, also called GAS (Generalized Audit Software). Some examples of these GAS are ACL (Audit Command Language) and IDEA. However, over time, DEA can also be implemented with other software, such as spreadsheets. Our research is a qualitative study, more specifically descriptive qualitative. In this study we use primary data obtained from interviews with auditors who have used audit software, ACL, IDEA and MS Excel-based audit applications. In addition we use secondary data from various literatures. Our results illustrate the strengths and weaknesses of each of the audit software and its application in the practical world of auditing